Un marché de Pierre Lochon pour l'image de la confrérie Saint-Joseph des charpentiers (1682) = An agreement between engraver Pierre Lochon and the Confraternity of the Carpenters of Paris commissioning a print (1682) - Mathis, Rémi 1982- (2020)
On 13th September 1683, by a notarial deed prepared by De Troyes in Paris (AN, MC, XLVI, 134), Pierre Lochon undertook to engrave an image representing Saint Joseph for the Confraternity of the Carpenters of Paris. He submitted a drawing, amended at the request of the commissioning parties, and will have to submit his work for approval. He is paid 120 livres, half of which is paid on commission and has five and a half months at his disposal.